HbA1c, fasting and 2-hour plasma glucose in current, ex-, and non-smokers: a meta-analysis - Soulimane, A.; Simon, D.; Herman, W.; Lange, C.; Lee, Crystal; Colagiuri, S.; Shaw, J.; Zimmet, P.; Magliano, D.; Ferreira, S.; Dong, Y.; Zhang, L.; et al. (Springer Verlag, 2014)
Aims/Hypothesis: The relationships between smoking and glycaemic variables have not been well explored. We compared HbA1c, fasting plasma glucose (FPG) and 2 h plasma glucose (2H-PG) in current, ex- and never-smokers. Methods: This meta-analysis used individual data from 16,886 men and 18,539 women without known diabetes in 12 DETECT-2 consortium studies and in the French Data from an Epidemiological Study on the Insulin Resistance Syndrome (DESIR) and Telecom studies. Means of three glycaemic variables in current, ex- and never-smokers were modelled by linear regression, with study as a random factor. The I2 statistic was used to evaluate heterogeneity among studies. Results: HbA1c was 0.10% (95% CI 0.08, 0.12) (1.1 mmol/mol [0.9, 1.3]) higher in current smokers and 0.03% (0.01, 0.05) (0.3 mmol/mol [0.1, 0.5]) higher in ex-smokers, compared with never-smokers. For FPG, there was no significant difference between current and never-smokers (−0.004 mmol/l [−0.03, 0.02]) but FPG was higher in ex-smokers (0.12 mmol/l [0.09, 0.14]). In comparison with never-smokers, 2H-PG was lower (−0.44 mmol/l [−0.52, −0.37]) in current smokers, with no difference for ex-smokers (0.02 mmol/l [−0.06, 0.09]).There was a large and unexplained heterogeneity among studies, with I2 always above 50%; I2 was little changed after stratification by sex and adjustment for age and BMI. In this study population, current smokers had a prevalence of diabetes that was 1.30% higher as screened by HbA1c and 0.52% lower as screened by 2H-PG, in comparison with never-smokers. Conclusion/interpretation: Across this heterogeneous group of studies, current smokers had a higher HbA1c and lower 2H-PG than never-smokers. This will affect the chances of smokers being diagnosed with diabetes.